Pengaruh Pemberian Teh Bunga Telang (Clitoria ternatea) tehadap Kadar Gula Darah Peserta Didik dan Guru di SMA Bumi Cendekia - Ilham Rasyid Fa Sa’dan; Arkoun Ali Fatih; Kinaura Mehrunisa Putri; Ashabiq Yudhy Avanda; Taufik Arianto; Tathmainul Qulub; Rifatul Adabiyah (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2025)
Hyperglycemia, characterized by elevated blood glucose levels, is a primary indicator for diagnosing diabetes mellitus. This study aims to evaluate the effect of butterfly pea flower tea (Clitoria ternatea) consumption on reducing blood glucose levels among students and teachers at Bumi Cendekia High School. The experimental research involved 10 participants who consumed butterfly pea flower tea daily for seven consecutive days. Blood glucose levels were measured both before and after the intervention. The results demonstrated a significant average reduction in blood glucose levels, with the highest decrease recorded at 31 mg/dL. Statistical analysis using an independent t-test confirmed the tea's effectiveness in lowering blood glucose levels, with a significance value of (p < 0.05). These findings suggest that butterfly pea flower tea may serve as a promising natural alternative for managing blood glucose levels.